2012
DOI: 10.1021/bc3005254
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of Gram Positive and Gram Negative Bacteria with the Antimicrobial Peptide (KLAKLAK)2 Conjugated to the Hydrophilic Photosensitizer Eosin Y

Abstract: We test the hypothesis that the antimicrobial peptide (KLAKLAK)(2) enhances the photodynamic activity of the photosensitizer eosin Y upon conjugation. The conjugate eosin-(KLAKLAK)(2) was obtained by solid-phase peptide synthesis. Photoinactivation assays were performed against the Gram-negative bacteria Escherichia coli , Pseudomonas aeruginosa , and multidrug resistant Acinetobacter baumannii AYE, as well as the Gram-positive bacteria Staphylococcus aureus , and Staphylococcus epidermidis . Partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 36 publications
5
77
2
1
Order By: Relevance
“…Since ROS formation can induce damage to bacterial membranes, [16, 40] we then evaluated whether the diffusible and short-lived ROS generated by the ATCUN–AMPs bound to copper ions (Cu–ATCUN–AMP) could potentially destabilize the bacterial membrane through oxidative stress. The oxidative damage brought about by ROS production was assessed by measuring lipid peroxidation in small unilamellar vesicles (SUVs) that mimic the E. coli outer membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ROS formation can induce damage to bacterial membranes, [16, 40] we then evaluated whether the diffusible and short-lived ROS generated by the ATCUN–AMPs bound to copper ions (Cu–ATCUN–AMP) could potentially destabilize the bacterial membrane through oxidative stress. The oxidative damage brought about by ROS production was assessed by measuring lipid peroxidation in small unilamellar vesicles (SUVs) that mimic the E. coli outer membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of photosensitizers to AMPs have led to improved antimicrobial action due to the production of ROS upon irradiation with visible light. [1618] …”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al reported that the peptide (KLAKLAK) 2 greatly enhances the photodynamic activity of eosin Y, and that eosin-(KLAKLAK) 2 can photoinactivate Gram-positive and Gram-negative strains to a similar extent [41]. Estevão et al have shown that eosin Y and its ester derivatives in micelles are promising photosensitizers for photodynamic applications because increasing hydrophobicity of the photosensitizer promotes a higher interaction with biological membranes [42].…”
Section: Discussionmentioning
confidence: 99%
“…The possibilities of spatially localized generation of reactive oxygen species (ROS) in response to irradiation are only just beginning to be explored, despite the more than 100-y history of phototherapy in modern medicine (1), and are already in the clinic in the form of photodynamic therapy (PDT) for cancers of the skin, esophagus, and organ linings, actinic keratosis, and acne (2,3). Photodynamic destruction of pathogenic bacteria, viruses, and fungi is also under investigation for antibiowarfare applications, passive sanitization of hospital surfaces under room light, and active sanitization of medical devices such as catheters (4)(5)(6)(7)(8). A major drawback of systemically dosed PDT photosensitizers, which are primarily porphyrins or their prodrugs (9), is their accumulation in the skin and eyes leading to long-lasting (weeks to months) posttherapeutic photosensitivity (10).…”
mentioning
confidence: 99%